2018
DOI: 10.5194/esurf-6-1023-2018
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of structure from motion photogrammetry and the traversing micro-erosion meter for measuring erosion on shore platforms

Abstract: Abstract. For decades researchers have used the micro-erosion meter and its successor the traversing micro-erosion meter to measure micro-scale rates of vertical erosion (downwearing) on shore platforms. Difficulties with “upscaling” of micro-scale field data in order to explain long-term platform evolution have led to calls to introduce other methods which allow for the measurement of platform erosion at different scales. Structure from motion photogrammetry is fast emerging as a reliable, cost-effective tool… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…On the other hand, in the perfect lab setting with 16 photos from ∼1.5 m, the detrended flat carpet around the pebbles achieved a standard deviation of 0.2 mm (33,371 points), similar to other SfM-MVS studies using large numbers of carefully collected images (e.g., Cullen et al, 2018;Verma and Bourke, 2019). These standard deviations from detrended flat surfaces represent a best-case scenario, whereas, in our field setting, the vertical uncertainty on the complex, overlapping pebbles is likely higher.…”
Section: Additional Data Dimensions From Point Cloudssupporting
confidence: 75%
“…On the other hand, in the perfect lab setting with 16 photos from ∼1.5 m, the detrended flat carpet around the pebbles achieved a standard deviation of 0.2 mm (33,371 points), similar to other SfM-MVS studies using large numbers of carefully collected images (e.g., Cullen et al, 2018;Verma and Bourke, 2019). These standard deviations from detrended flat surfaces represent a best-case scenario, whereas, in our field setting, the vertical uncertainty on the complex, overlapping pebbles is likely higher.…”
Section: Additional Data Dimensions From Point Cloudssupporting
confidence: 75%
“…Norwick and Dexter, 2002;Bruthans et al, 2018). There are a number of areal surface roughness and geomorphometric parameters that can be applied to quantify rock breakdown (Leach, 2013;Lai et al, 2014;Davis et al, 2015;Du Preez, 2015;Trevisani and Rocca, 2015;Verma and Bourke, 2017). The ability to quantify surface change across an area rather than limited to specific points will aid interpretation of the causal links between controls and resultant landform development.…”
Section: Importance Of Microtopographic Data In Rock Breakdownmentioning
confidence: 99%
“…This slightly improved the accuracy of wear facet identification and measurement, however, high levels of surface noise meant that the deviation of these measurements from those derived from the SLS reference models was still beyond the limits of acceptability for the performance of OFA. Similarly, although studies of 3D topographic changes in the geosciences have reported the capacity of SfM approaches to detect changes in the profile of surfaces at a submillimetre level, the detection of scratches and features smaller than 0.3 mm was inconsistent and fell outside the limits of detection of the method used in a recent study (Cullen, Verma, & Bourke, 2018).…”
Section: Discussionmentioning
confidence: 96%